CLOUD COMPUTING AND ITS EFFECT ON PERFORMANCE EXCELLENCE AT HIGHER EDUCATION INSTITUTIONS IN EGYPT (AN ANALYTICAL STUDY) - Hussein, Ahmed; Mohamed, Omar (European Scientific Journal, ESJ, 2015)
This period is marked by current financial crisis and challenges related to many growing needs. Consequently, universities are facing problems in providing necessary information technology (IT) support for fulfilling excellence in performance. More specifically, the best practices of Cloud Computing need to be considered within higher education institutions. Therefore, the current study aimed at investigating cloud computing, in terms of: (1) definition; (2) its most important principles; (3) models; and (4) benefits of its use to fulfill performance excellence in higher education institutions. This involves shedding light on cloud computing models and the possibility of its use in higher education institutions, and exploring the effect of using cloud computing in achieving performance excellence there. Additionally, the study aimed at clarifying the challenges and obstacles that face cloud computing. To reach these objectives, the researchers employed a qualitative research methodology for collecting and analyzing data. The study concluded some results, most important of which are: (1) there is a significant relationship between cloud computing and excellence of performance as cloud computing mainly aims at achieving tasks quickly with the least effort and cost. Personnel, customers, innovation and leadership are the core elements to achieve excellence in higher education institutions, and are major components of cloud computing. These positive results support the use of Cloud-Computing solutions in universities and improving knowledge in this field and providing a practical guide adaptable to the university structure.